Amino acids and their derivatives mediating defense priming and growth tradeoff. (October 2022) - Cai, Jianghua; Aharoni, Asaph
Abstract: Plant response to pathogens attacks generally comes at the expense of growth. Defense priming is widely accepted as an efficient strategy used for augmenting resistance with reduced fitness in terms of growth and yield. Plant-derived small molecules, both primary as well as secondary metabolites, can function as activators to prime plant defense. Amino acids and their derivatives regulate numerous aspects of plant growth and development, and biotic and abiotic stress responses. In this review, we discuss the recent progress in understanding the roles of amino acids and related molecules in defense priming and their link with plant growth. We also highlight some of the outstanding questions and provide an outlook on the prospects of 'engineering' the tradeoff between defense and growth in plants.